Cardiolipin Structure and Oxidation Are Affected by Ca2+ at the Interface of Lipid Bilayers - Miranda, Érica G. A.; Araujo-Chaves, Juliana C.; Kawai, Cintia; Brito, Adrianne M. M.; Dias, Igor W. R.; Arantes, Jeverson T.; Nantes-Cardoso, Iseli L. (Frontiers in Chemistry, 2020)
Ca2+-overload contributes to the oxidation of mitochondrial membrane lipids and associated events such as the permeability transition pore (MPTP) opening. Numerous experimental studies about the Ca2+/cardiolipin (CL) interaction are reported in the literature, but there are few studies in conjunction with theoretical approaches based on ab initio calculations. In the present study, the lipid fraction of the inner mitochondrial membrane was modeled as POPC/CL large unilamellar vesicles (LUVs). POPC, CL and POPC/CL LUVs were challenged by singlet molecular oxygen using the anionic porphyrin TPPS4 as a photosensitizer and by free radicals produced by Fe2+-citrate. Calcium ion favored both types of lipid oxidation in a lipid composition-dependent manner. In membranes containing predominantly or exclusively POPC, Ca2+ increased the oxidation at later reaction times while the oxidation of CL membranes was exacerbated at the early times of reaction. Considering that Ca2+ interaction affects the lipid structure and packing, density functional theory (DFT) calculations were applied to the Ca2+ association with totally and partially protonated and deprotonated CL in the presence of water. The interaction of totally and partially protonated CL head groups with Ca2+ decreased the intramolecular P-P distance and increased the hydrophobic volume of the acyl chains. Consistently with the theoretically-predicted effect of Ca2+ on CL, in the absence of pro-oxidants, giant unilamellar vesicles (GUVs) challenged by Ca2+ formed buds and many internal vesicles. Therefore, Ca2+ induces changes in CL packing and increases the susceptibility of CL to the oxidation promoted by free radicals and excited species.